2015
DOI: 10.1245/s10434-015-4630-0
|View full text |Cite
|
Sign up to set email alerts
|

Local Control in Ewing Sarcoma of the Chest Wall: Results of the EURO-EWING 99 Trial

Abstract: Background. Primary Ewing sarcoma (ES) can sometimes present as a chest-wall tumor. Multidisciplinary management, including chemotherapy and local treatment consisting of surgery, radiotherapy (RT), or both, has improved the survival of patients with localized ES; however, the best approach to achieving local control remains controversial.Methods. We retrospectively analyzed data from 198 patients with non-metastatic ES of the chest wall, who were registered in the database of the German Society of Pediatric H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 39 publications
5
39
1
Order By: Relevance
“…Askin's tumor originates from the osseous structures of the chest wall including the ribs, scapula, clavicle, or sternum and most often presents with a mass in the chest wall and symptoms suggestive of pneumonia such as cough, fever, dyspnea, weight loss, and pleural effusions. 66 …”
Section: Clinical Presentationmentioning
confidence: 99%
“…Askin's tumor originates from the osseous structures of the chest wall including the ribs, scapula, clavicle, or sternum and most often presents with a mass in the chest wall and symptoms suggestive of pneumonia such as cough, fever, dyspnea, weight loss, and pleural effusions. 66 …”
Section: Clinical Presentationmentioning
confidence: 99%
“…54.2%,P = 0.142) concluding that microscopically complete tumor resection would be the best way to achieve local control and additional RT would be useful for incomplete resections. 16 In the past, there was a general recommendation for Ewing sarcomas of the ribs stating that a complete resection of the rib is necessary due to possible bone marrow infiltration and the risk of tumor recurrence, but a recent study showed no difference between partial or complete resections of the affected rib. 16 EFS: 64%).…”
Section: Survivors (N) Discussionmentioning
confidence: 99%
“…Complete resection is an important goal. Bedetti et al showed in an analysis of 198 patients with chest wall Ewing sarcoma, no statistically significant difference between R 0 (EFS: 69%) or R 1/2 resections (EFS: 54.2%, P = 0.142) concluding that microscopically complete tumor resection would be the best way to achieve local control and additional RT would be useful for incomplete resections . In the past, there was a general recommendation for Ewing sarcomas of the ribs stating that a complete resection of the rib is necessary due to possible bone marrow infiltration and the risk of tumor recurrence, but a recent study showed no difference between partial or complete resections of the affected rib .…”
Section: Discussionmentioning
confidence: 99%
“…Bedetti et al showed in an analysis of 198 patients with chest wall Ewing sarcoma, no statistically significant difference between R 0 (EFS: 69%) or R 1/2 resections (EFS: 54.2%, P = 0.142) concluding that microscopically complete tumor resection would be the best way to achieve local control and additional RT would be useful for incomplete resections . In the past, there was a general recommendation for Ewing sarcomas of the ribs stating that a complete resection of the rib is necessary due to possible bone marrow infiltration and the risk of tumor recurrence, but a recent study showed no difference between partial or complete resections of the affected rib . This finding is supported by Sirvent et al analyzing 57 patients with nonmetastatic Ewing sarcoma of the ribs enrolled in the studies of the French Society of Pediatric Oncology showing no difference in survival in patients with microscopic tumor residuals ( n = 15, EFS: 68%) compared with those with negative tumor margins ( n = 40, EFS: 64%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation